The effect of Portuguese nation brand on cognitive brand image: Portuguese and Canadian comparison - Loureiro, S. M. C.; Veríssimo, A.; Cayolla, R. (International Journal of Management Cases, 2013)
The Anholt et al.’s (2008) model proposes six components to measure a national brand: Exports, Culture and Heritage, Governance, Investment and Immigration, Tourism, and People. This study intends to analyze the effect of each of those components associated to Portugal on cognitive brand image perceived by Portuguese and foreign (Canadian) people. The survey, based on literature review, was gathered in Portugal and Canada. In the Portuguese sample, findings demonstrate favourable classifications for the willingness to use Portuguese products and the country's contribution to innovation in science. However, the Portuguese do not perceive the country as cutting-edge. The Canadian respondents see Portugal as a creative country. On a less favourable note, Canadian respondents have a lower classification of Portugal's contribution to innovation in science, which sharply contrasts Portuguese results. Furthermore, Portugal is also less favourable seen as an innovative and cutting-edge country. Regarding the causal path analysis, for Portuguese respondents Investment and Immigration, Tourism, and People contribute significantly to a favourable cognitive image. For the Canadian sample population, Tourism and People have a significant impact on cognitive image. Globally, Portugal tends to be positively associated to tourism, culture, heritage, and people.